Space-based observational constraints for 1-D fire smoke plume-rise models - Val Martin, Maria; Kahn, Ralph A.; Logan, Jennifer A.; Paugam, Ronan; Wooster, Martin; Ichoku, Charles (Journal of Geophysical Research: Atmospheres, 2012)
We use a plume height climatology derived from space‐based Multiangle Imaging Spectroradiometer (MISR) observations to evaluate the performance of a widely used plume‐rise model. We initialize the model with assimilated meteorological fields from the NASA Goddard Earth Observing System and estimated fuel moisture content at the location and time of the MISR measurements. Fire properties that drive the plume‐rise model are difficult to constrain, and we test the model with four estimates each of active fire area and total heat flux, obtained from Moderate Resolution Imaging Spectroradiometer (MODIS) fire radiative power (FRP) thermal anomalies available for each MISR plume and other empirical data. We demonstrate the degree to which the fire dynamical heat flux (related to active fire area and sensible heat flux) and atmospheric stability structure influence plume rise, although entrainment and possibly other less well constrained factors are also likely to be significant. Using atmospheric stability conditions, MODIS FRP, and MISR plume heights, we find that smoke plumes reaching high altitudes are characterized by higher FRP and weaker atmospheric stability conditions than those at low altitude, which tend to remain confined below the boundary layer, consistent with earlier results. However, over the diversity of conditions studied, the model simulations generally underestimate the plume height dynamic range observed by MISR and do not reliably identify plumes injected into the free troposphere, key information needed for atmospheric models to simulate smoke dispersion. We conclude that embedding in large‐scale atmospheric studies an advanced plume‐rise model using currently available fire constraints remains a difficult proposition, and we propose a simplified model that crudely constrains plume injection height based on two main physical factors for which some observational constraints often exist. Field experiments aimed at directly measuring fire and smoke plume properties in detail are likely to produce the next major advances in plume‐rise modeling. Key Points A plume‐rise model is evaluated with empirical and satellite observations Plume model does not reproduce the heights with available fire constraints We propose two simplified methods to develop an injection height parameterization